2023
DOI: 10.1002/hbm.26328
|View full text |Cite
|
Sign up to set email alerts
|

Gene transcriptional expression of cortical thinning during childhood and adolescence

Abstract: The cognitive and behavioral development of children and adolescents is closely related to the maturation of brain morphology. Although the trajectory of brain development has been depicted in detail, the underlying biological mechanism of normal cortical morphological development in childhood and adolescence remains unclear. By combining the Allen Human Brain Atlas dataset with two single‐site magnetic resonance imaging data including 427 and 733 subjects from China and the United States, respectively, we per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
2
0
0
Order By: Relevance
“…A recent study showed that cortical thinning during development is associated with genes expressed predominantly in astrocytes, microglia, excitatory and inhibitory neurons (Zhou et al, 2023). We observed faster cortical thinning of default-mode and visual networks, consistent with previous studies (Ball, Seidlitz, Beare, et al, 2020;Zhou et al, 2023).…”
Section: Implications For Cortical Thinningsupporting
confidence: 92%
See 1 more Smart Citation
“…A recent study showed that cortical thinning during development is associated with genes expressed predominantly in astrocytes, microglia, excitatory and inhibitory neurons (Zhou et al, 2023). We observed faster cortical thinning of default-mode and visual networks, consistent with previous studies (Ball, Seidlitz, Beare, et al, 2020;Zhou et al, 2023).…”
Section: Implications For Cortical Thinningsupporting
confidence: 92%
“…A recent study showed that cortical thinning during development is associated with genes expressed predominantly in astrocytes, microglia, excitatory and inhibitory neurons (Zhou et al, 2023). We observed faster cortical thinning of default-mode and visual networks, consistent with previous studies (Ball, Seidlitz, Beare, et al, 2020;Zhou et al, 2023). Apparent thinning may be a result of the macrostructural shift in the boundary between grey matter and white matter, in this scenario due to myelin encroachment into the cortex (Mournet et al, 2020;Natu et al, 2019).…”
Section: Implications For Cortical Thinningsupporting
confidence: 90%